Capacity Development Services and the Demand Market in Albanian Tourism Sector - BROKAJ, Rezarta (European Journal of Sustainable Development, 2015)
Over the last 20 years the role of tourism has been increasingly recognized as an important development strategy, considering its importance in creating positive economical effects in worldwide level. Sustainability has become nowadays a principle of development and obviously of tourism development.Sustainable tourism is one of the main development priorities of local, national and international authorities to ensure long term success on a global market.One of the main reasons in sustainability of tourism development in Albania is that almost planners, operators and local community could not have created a connection through different dimensions of the sustainability.The paper explores the need and demand for building Albania`s private sector capacity for tourism development. This study was run in the most important market actors which operate in the tourism sector in Albania, especially focusing in clients of capacity development services. Questionnaire was used to collect data from the most important tourism operators, that use these services.The aim was to examine their views on tourism development, in an attempt to establish overall desired directions for tourism development and to suggest effective tourism strategies and policies to reinforce positive outcomes and alleviate problems resulting from previous unplanned tourism development.According to the survey, results showed the availability of capacity building services, the links with local and international service providers, their preferred service delivery mechanisms and the barriers that exist in this market.Hence understanding barriers of capacity development services can help to all the actors for future planning to achieve sustainable tourism development. Keywords: capacity development, tourism operators, sustainable development, service quality .